A Damage Constitutive Model of Rock under Hydrochemical Cyclic Invasion. (8th August 2020) - Sun, Lunan; Zhang, Yu; Qin, Zhe; Wang, Tengfei; Zhang, Sheng
Abstract : In order to analyze the stability of water-related materials, the deterioration and damage of rock strength due to circulating water intrusion in an open tailings pond were studied. Uniaxial compression tests were carried out for rocks under different hydrochemical environments and varying numbers of invasion cycles. Results show that, with increasing number of cycle times, rock peak strength and elastic modulus gradually decrease and the acidity and alkalinity of the soaking solution also degrades rock strength. The curve of the number of cycles, acidity, alkalinity, peak strength, and elastic modulus is fit numerically. Based on the principle of damage mechanics, a hydraulic-chemistry-mechanics (HCM) coupling damage variable is defined. Based on the theory of microbody strength distribution, the constitutive equation for rock damage under the coupled effect of water chemistry and cyclic water invasion is established. The results verify the validity of the established damage constitutive model.